2016
DOI: 10.1080/09613218.2016.1226610
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of indoor temperatures in new-build housing

Abstract: Despite growing concerns about overheating, there is a lack of evidence regarding the scale of the problem, particularly in contemporary UK housing. This paper presents the results of a meta-analysis of indoor temperatures in selected low-energy housing.Temperature data recorded at 5 minute intervals in 60 dwellings across 19 demonstration projects (2012)(2013)(2014) were collated and analysed to investigate the prevalence of overheating.Findings evidence high summertime temperatures, with 27% of living rooms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
(48 reference statements)
0
12
1
Order By: Relevance
“…Climate change is not only associated with rising outdoor temperatures, but also increases in the air temperature of the indoor environment (i.e., buildings, houses) [ 13 ], particularly during prolonged periods of hot weather (e.g., heat waves) [ 14 ]. Factors such as modern building design and insulation (buildings being more air tight, more efficient window designs, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Climate change is not only associated with rising outdoor temperatures, but also increases in the air temperature of the indoor environment (i.e., buildings, houses) [ 13 ], particularly during prolonged periods of hot weather (e.g., heat waves) [ 14 ]. Factors such as modern building design and insulation (buildings being more air tight, more efficient window designs, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…For example, some post occupancy research has suggested that overheating risk is exacerbated by increases in insulation levels and air tightness. 8,[16][17][18][19] At the same time, counter examples exist: lack of roof insulation is a common cause of overheating in older properties 7 and in the European heatwave of 2003 this omission was specifically identified as a risk factor for overheating. 20 The Building Performance Evaluation project of 76 homes drew inconclusive results as to whether homes with higher insulation levels were more at risk: individual instances of overheating were found but robust conclusions could not be drawn.…”
Section: Building Design and Overheating Riskmentioning
confidence: 99%
“…For example, some post occupancy research has suggested that overheating risk is exacerbated by increases in insulation levels and air tightness. 8,16–19…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review Wang et al (2017) document the breadth of work that analyses the energy performance of PH but bemoan the lack of studies that investigate energy efficiency and IEQ in the same. Some comprehensive and prolonged studies have documented indoor temperature profiles in PH homes, while also reporting on CO2 and humidity levels (McGill et al 2017) and have also documented overheating which is a growing concern in today's, and future, climates. Low energy housing, characterised by high levels of insulation and airtightness are particularly susceptible to overheating (Kinnane et al 2016b), and low energy housing in the UK with MVHR exhibit higher minimum and average summertime temperatures (McGill et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some comprehensive and prolonged studies have documented indoor temperature profiles in PH homes, while also reporting on CO2 and humidity levels (McGill et al 2017) and have also documented overheating which is a growing concern in today's, and future, climates. Low energy housing, characterised by high levels of insulation and airtightness are particularly susceptible to overheating (Kinnane et al 2016b), and low energy housing in the UK with MVHR exhibit higher minimum and average summertime temperatures (McGill et al 2017). Similarly overheating has been reported in a number of other PH studies in southern (Fokaides et al 2016) and northwestern European climates (McLeod et al, 2013, Colclough et al, 2017b.…”
Section: Introductionmentioning
confidence: 99%